Research of the opportunity to use sludge wastes of ferrovanadium production as pigments for silicate paints - I V, Starostina; M M, Kosukhin; M M, Simonov; Yu.L, Starostina (International Journal of Engineering and Technology, 2018)
The article considers the urgent problem of formation, storage and recycling of sludge materials of various compositions, generated as a result of industrial enterprises wastewater treatment and sanitation. It is pointed out that in spite of a lot of designs concerning the wastewater neutralization sludges recycling, the share of their efficient usage is still negligible. So, one of the most relevant trends of nature protection activity and the rational use of natural resources is developing a technology of these wastes reclamation and applying them for useful products manufacturing. The research of chemical, mineral and grain composition of ferrovanadium production sludge wastes, generated at waste waters neutralization at the Â«EVRAZ Vanadii TulaÂ», Tula, Russia, has been carried out. A method of obtaining pigments for silicate paints on the basis of these sludges has been considered. The influence of the sludges' thermal treatment conditions on their mineral composition and the properties of paints based on them has been evaluated. The pigments content varies from 1 to 3 %. It has been demonstrated that the most promising is the usage of initial sludges and heat-treated at temperature 1000Â°Ð¡ sludges as pigments for high-performance silicate paints.Â